A retrospective study of disease prevalence in domestic animals of hill region - GURAV, AMOL; JANA, C; UPADHYAY, D; DANGI, S S; SHARMA, A K; GAUTAM, S (The Indian Journal of Animal Sciences, 2018)
The present study was aimed at recording the prevalence and types of various disorders in the domestic animals of hill region. The retrospective data of three years (2014–16) was collected from outpatient case record of veterinary dispensary unit, Indian Veterinary Research Institute, Mukteswar. A total of 577 cases were recorded during the period, of which, majority of cases were of cattle followed by goats. The autumn observed highest percentage of cases with lowest % in winter. Ectoparasitic infestation, endoparasitism, diarrhea and weakness were noticed as major clinical problems in cattle. Among infectious diseases, mastitis prevailed most among all other diseases of cattle. Haematuria, injury/wound and repeat breeding were also recorded frequently in cattle. Highest prevalence (70.58%) of haematuria was observed in the age group of 5–10 years. Retrospective epidemiological data on goats revealed that ecto-endoparasitic infestation and stomatitis were major diseases/disorders observed among goats of the region. About 46.92% of goat patients were recorded in autumn while winter observed 10.05% cases only. The retrospective epidemiological data generated during the present study helps in better understanding of the animal disease pattern in temperate climatic conditions, which will further help in implementing control measures against infectious and non-infectious diseases.